The inhibition of reactive oxygen species (ROS) by antioxidants inhibits the release of an autophagy marker in ectopic endometrial cells - Huixia Lu; Hong Hu; Yi Yang; Shaobo Li (Elsevier, 2020)
Objective: The aim of this study was to evaluate the role of oxidative stress and reactive oxygen species (ROS) in the pathogenesis of endometriosis (EMs) and to investigate the role of antioxidant therapy on autophagy and the outcome of EMs. Materials and methods: Experimental rats were given an peritoneal perfusion of N-acetyl-l-cysteine (NAC, 200 mg/kg) or catalase (CAT, 2000 U/mL). Immunofluorescence was then used to detect microtubule-associated protein light chain 3 (LC3). Western blotting was used to determine the levels of Beclin-1 protein while enzyme-linked immunosorbent assays (ELISAs) were used to measure ROS levels after treatment. Results: Fluorescent in situ hybridization showed that NAC and CAT influenced the levels of LC3, an autophagy marker; there were significantly lower levels of LC3 fluorescence in the EMs group (surgical group) of rats compared with controls (p < 0.05). Western blot analysis revealed a downregulation of Beclin-1 protein in both the NAC and CAT groups (p < 0.05) while ELISA revealed significantly lower levels of ROS in the NAC and CAT groups (p < 0.05). Conclusion: The antioxidants NAC and CAT significantly reduced levels of the autophagy marker LC3 and caused levels of Beclin-1 to significantly decrease. Consequently, antioxidant therapy shows potential for the future treatment of EMs. Keywords: Autophagy, Reactive oxygen species, ROS, Endometriosis, Antioxidant